ADVANCING E-COMMERCE LOGISTICS IN GUANGDONG'S RURAL AREAS: A FRAMEWORK FOR ASSESSMENT - Ferreira , Marco (Ayden International Journal of Education and Social sciences, 2024)
China's rural e-commerce industry has experienced significant growth, driven by government support and industrial policies. Policies such as the "Circular on the creation of demonstration zones for agricultural modernization in 2022" and "Opinions on strengthening the construction of county commercial systems to promote rural consumption" have provided a favorable environment for rural e-commerce development. Guangdong Province, in particular, is actively working to enhance its rural e commerce industry, expanding its presence in 53 demonstration counties and prioritizing rural consumption as a key strategy for economic growth. To achieve high-quality development in rural e commerce, it is essential to focus on improving the quality of express delivery services and strengthening logistics support for rural rejuvenation. This paper explores the significance of logistics support in promoting the high-quality development of rural e commerce in Guangdong Province.